Evaluation of Anthelmintic activity of Vitex trifolia Linn leaves against Pheretima posthuma - Thenmozhi, S (International Journal of Pharmaceutical & Biological Archive, 2014)
Evaluation of Anthelmintic activity of Vitex trifolia Linn leaves against Pheretima posthuma